Leveraging Qualified Residential Treatment Program requirements to facilitate data driven decision-making: a guide for child welfare administrators. Issue 2 (15th March 2023) - Quiros, Julian; Solomon, Phyllis
ABSTRACT: Family First Prevention Services Act has adjusted the reimbursement process for youth placed in residential facilities where only those placed in facilities designated as Qualified Residential Treatment Programs (QRTP) will be eligible for reimbursement. Addressed is a component of QRTP requirements, the assessment of the child being placed with age-appropriate, evidence-based, validated, functional assessment tool. Little guidance is available for system administrators and stakeholders as to what to consider and how to select an appropriate tool; thus, this paper discusses trauma instrument attributes and advocates for the use of data collection that aids decision-making and has the potential to improve services.